2015
DOI: 10.1016/j.bpj.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

High Cholesterol Obviates a Prolonged Hemifusion Intermediate in Fast SNARE-Mediated Membrane Fusion

Abstract: Cholesterol is essential for exocytosis in secretory cells, but the exact molecular mechanism by which it facilitates exocytosis is largely unknown. Distinguishing contributions from the lateral organization and dynamics of membrane proteins to vesicle docking and fusion and the promotion of fusion pores by negative intrinsic spontaneous curvature and other mechanical effects of cholesterol have been elusive. To shed more light on this process, we examined the effect of cholesterol on SNARE-mediated membrane f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 79 publications
2
65
0
Order By: Relevance
“…Clustering of t-SNAREs has been reported to be important for promoting membrane fusion and these clusters are cholesterol-dependent (49). Consistently, the Haynes group showed that platelet membrane cholesterol directly affects cargo release from platelets by affecting fusion pore formation, dilation, and full fusion (50).…”
Section: Acylation's Effects On T-snaressupporting
confidence: 50%
“…Clustering of t-SNAREs has been reported to be important for promoting membrane fusion and these clusters are cholesterol-dependent (49). Consistently, the Haynes group showed that platelet membrane cholesterol directly affects cargo release from platelets by affecting fusion pore formation, dilation, and full fusion (50).…”
Section: Acylation's Effects On T-snaressupporting
confidence: 50%
“…Indeed, such two-color experiments may provide the only conclusive assessment of the presence of hemifusion in other in vitro fusion assays 18,20 . However, hemifusion can reliably be detected in single-color SUV-SBL experiments monitoring lipid release alone 22,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Others have fused v-SUVs to planar bilayers reconstituted with t-SNAREs [15][16][17][21][22][23][24][25][26][27]29 . The planar geometry of the target (t-SNARE containing) bilayer better mimics the physiological fusion process of small, highly curved vesicles with a flat plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intermediates include tethering and docking of the two membranes to one another, initiation of fusion where a point like protrusion occurs in one of the bilayers, hemifusion stalk formation which may progress into an extended hemifusion diaphragm and then to a fusion pore, Figure 1.1 (Martens & McMahon, 2008;Chernomordik & Kozlov, 2008). In vitro fusion assays also appear to have a dead end off pathway stable hemifusion intermediate that does not lead to the opening of a fusion pore (Diao, et al, 2012;Kreutzberger, et al, 2015;Chlanda, et al, 2016). …”
Section: Membrane Fusionmentioning
confidence: 99%